Multifunctional hard coatings based on CrNx for temperature sensing applications - Ferreira, Armando José Barros (2021)
This paper presents reports on the preparation of a multifunctional coating system, CrNx, with temperature sensing capability. A systematic study of the thermo-resistive effect of chromium nitride (CrNx) thin films with a negative temperature coefficient of resistance (TCR) has been carried out. The CrNx nanostructures were grown by reactive magnetron sputtering under distinct Ar+N2 conditions. To confer a zigzag columnar morphology to the CrNx we explored the oblique angle deposition technique. The structural properties have been studied through X-ray diffraction and Scanning Electron Microscopy. The thermo-resistive response was evaluated by measuring the electrical resistivity as a function of temperature by the twopoint method. The results observed for the CrNx films produced with N2 flux between 4 and 8 sccm present an stable and negative TCR. Values of -9.1710-4 , -5.3110-3 , and -1.47610-2 were observed for the films grown with 4, 6, and 8 sccm, respectively. The grain-boundary was used to theoretically describe our results. The results open new technological possibilities for the application of CrNx coatings for esistive temperature detector (RTD) systems.